DIFFERENTIAL EFFECTS OF ALLOXAN ON DIFFERENT BLOOD PARAMETERS IN DIABETEC INDUCED MALE WISTAR RATS - ANJALI SMITA,; ABHIJIT DUTTA, (International Journal of Pharma and Bio Sciences, 2015)
Alloxan is known for chemical induction of Type 1 Diabetes Mellitus (DM) through selective damage of β- cells of pancreas, thereby inducing hyperglycemic state in experimental animals. Adult male wistar rats were used as experimental models. Diabetes was induced by injecting alloxan monohydrate at a dose of 60 mg/kg body weight for three days daily. The physical parameters like body weight showed a significant decline whereas there was a rise in food consumption and water intake of the experimental animals. The blood parameters like blood glucose, SGPT, SGOT, and LDH and creatinine levels showed an increase. Blood glucose, LDH and creatinine showed a statistically significant result. However, SGPT and SGOT were statistically insignificant. The study indicates that physical and blood serum parameters might serve as a good indicator for the study of physiology and effects in alloxan induced diabetic rats.